2016
DOI: 10.1159/000452468
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Decision-Making for or against Adjuvant and Neoadjuvant Chemotherapy in Postmenopausal Hormone Receptor-Positive Breast Cancer Patients in the EvAluate-TM Study

Abstract: Background: Decision-making for or against neoadjuvant or adjuvant chemotherapy in postmenopausal patients with hormone receptor-positive breast cancer does not follow any clear guidelines, and some patients may unnecessarily undergo chemotherapy and be exposed to the associated toxicity. The aim of this study was to identify the patient population for whom this issue may bear relevance. Methods: Patients being treated with letrozole in the prospective multicenter noninterventional EvAluate-TM study were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this issue of Breast Care, Gaß et al [5] explore which HR-positive patients should receive adjuvant and neoadjuvant chemotherapy. The treatment of these patients is a challenge because they have a good prognosis but often do not respond to chemotherapy.…”
mentioning
confidence: 99%
“…In this issue of Breast Care, Gaß et al [5] explore which HR-positive patients should receive adjuvant and neoadjuvant chemotherapy. The treatment of these patients is a challenge because they have a good prognosis but often do not respond to chemotherapy.…”
mentioning
confidence: 99%
“…Other studies have also examined decision-making parameters for neoadjuvant chemotherapy in hormone receptor-positive patients. A large prospective noninterventional study in postmenopausal women showed that age, body mass index, tumor grade, HER2 status, and the fact that patients were taking concomitant medication were influencing factors in relation to decision-making for or against neoadjuvant chemotherapy 24 . Information about the patientʼs pCR status could further add to this list of influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our experience and previous studies, the number of lymph nodes is just one aspect of consideration for AC, some other factors (eg, general condition, economic status, comorbidities, toxicity of drug, etc) also play essential role in decision making. [11][12][13] Only when we take all these factors into consideration comprehensively rather than comparing the number or ratio of positive lymph nodes alone, can we make the best recommendation for patients with esophageal adenocarcinoma.…”
mentioning
confidence: 99%